Koinonia as Ecumenical Opening for Baptists - Hatch, Derek C. (The ecumenical review, 2019)
This article discusses a new opening for Baptists' role in multilateral ecumenical dialogue since the release of Baptism, Eucharist and Ministry. A shift of emphasis toward koinonia has embraced relationship as a model for ecumenical endeavours while maintaining a robust sense of the goal of visible unity. The article will discuss several ecumenical insights and further potential for Baptist ecumenical work as a result of the centrality of koinonia.